PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PEGAWAI PADA PUSAT PENDIDIKAN DAN PELATIHAN APARATUR PERDAGANGAN DEPOK - Aditya Purnama Putra; Fathan Arif (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the partial and simultaneous influence of the influence of the work environment and career development on job satisfaction of employees at the Depok Trade Apparatus Education and Training Center. This research method is quantitative and the sample was 67 respondents using a saturated sampling technique. Data analysis techniques use validity, reliability, classical assumptions, simple and multiple linear regression, correlation, determination, t test and test f. The research results show that: There is an influence of the work environment on employee job satisfaction with a simple regression equation Y = 8.636 + 0.798(X1). The correlation value is Rx1y = 0.853 with a strong and significant relationship level, the contribution of the influence of the work environment is 72.7% and the partial hypothesis test shows a tcount value of 13.170 > ttable 1.669, or a Sig value of 0.000 < 0.05. There is an influence of career development on employee job satisfaction with a simple regression equation Y = 6.431+0.846 (X2), a correlation value of Rx2y = 0.910 with a strong and significant relationship level, the contribution of the influence of career development on job satisfaction is 82.8% and partial hypothesis testing shows a tcount value of 17.693 > ttable 1.669, a Sig value of 0.000 < 0.05. There is a simultaneous influence of the work environment and career development on employee job satisfaction with a multiple regression equation of Y = 3.929+ 0.281(X1)+0.611(X2), a multiple correlation value of Rx12y = 0.924 with a strong relationship level, the contribution of the influence of the work environment and development career on job satisfaction of 85.5% and simultaneous hypothesis testing shows an Fcount value of 187.974 > Ftable 3.140, or a Sig value of 0.000 < 0.05.